2021
DOI: 10.3390/molecules26071861
|View full text |Cite
|
Sign up to set email alerts
|

Transcript Regulation of the Recoded Archaeal α-l-Fucosidase In Vivo

Abstract: Genetic decoding is flexible, due to programmed deviation of the ribosomes from standard translational rules, globally termed “recoding”. In Archaea, recoding has been unequivocally determined only for termination codon readthrough events that regulate the incorporation of the unusual amino acids selenocysteine and pyrrolysine, and for −1 programmed frameshifting that allow the expression of a fully functional α-l-fucosidase in the crenarchaeon Saccharolobus solfataricus, in which several functional interrupte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…However, since there are no α-L-fucosidase genes regulated by PRF in Bacteria and Eukarya, it has been suggested that this sophisticated mechanism of translational regulation preexisted in S. solfataricus and it was applied to the α-L-fucosidase gene for physiological reasons. Very recently, it has been found that fucA1 mRNA increases by 10 fold after S. solfataricus undergoes cold shock and in S. solfataricus cells grown in minimal medium containing the oligosaccharides of the hemicellulose xyloglucan (De Lise et al, 2021). Furthermore, this α-L-fucosidase has been shown to cooperate with other glycoside hydrolases from S. solfataricus for the hydrolysis of fucosylated xyloglucan oligosaccharides by removing the fucose moieties from this substrate with high efficiency in vitro (Curci et al, 2021).…”
Section: Programmed Ribosomal Frameshiftingmentioning
confidence: 99%
“…However, since there are no α-L-fucosidase genes regulated by PRF in Bacteria and Eukarya, it has been suggested that this sophisticated mechanism of translational regulation preexisted in S. solfataricus and it was applied to the α-L-fucosidase gene for physiological reasons. Very recently, it has been found that fucA1 mRNA increases by 10 fold after S. solfataricus undergoes cold shock and in S. solfataricus cells grown in minimal medium containing the oligosaccharides of the hemicellulose xyloglucan (De Lise et al, 2021). Furthermore, this α-L-fucosidase has been shown to cooperate with other glycoside hydrolases from S. solfataricus for the hydrolysis of fucosylated xyloglucan oligosaccharides by removing the fucose moieties from this substrate with high efficiency in vitro (Curci et al, 2021).…”
Section: Programmed Ribosomal Frameshiftingmentioning
confidence: 99%